Assessment of nutritional status and the variables affecting the nutritional status of human immunodeficiency virus positive children in antiretroviral therapy centre of J. A. group of hospitals, Gajra Raja medic - Gogia, Priya; Ambey, Ravi; Sahu, Saumya (International Journal of Contemporary Pediatrics, 2016)
Background:HIV-infected children are undernourished; an improvement in their nutritional status may significantly decrease their morbidity. Thus, determining the etiology and temporal course of malnutrition in children with HIV infection will be important for early intervention and development of re-feeding regimens. This cross-sectional study describes the nutritional status and the variables affecting it, among the children made vulnerable by HIV/AIDS. The objective of this study was to assess the nutritional status of the HIV positive children, and to study the variables affecting the nutritional status of HIV positive children. Methods: The study involved 84 HIV positive children of 18 months - 18 years age group in the ART centre of J. A. group of hospital, Gajra Raja medical college, Gwalior, Madhya Pradesh. Anthropometric measurements, birth and maternal characteristics, socio-economic and immunization profile, past illness were recorded. Z-scores were generated using WHO standards as indicators of nutritional status and variables were assessed by suitable statistical test. Results:Prevalence of under nutrition is very high particularly moderate and severe stunting (76.19%), moderate and severe underweight (71.42%), and moderate and severe wasting (38.09%) in under five years HIV positive children. While low height for age was observed in 60.31%, low weight for age in 34.92%, and low BMI for age was recorded in 20.63%, in 6-18 years age group. Besides HIV status, other significant determinants of nutritional outcomes include child factors, birth related factors, maternal level factors, socio-economic and past history of illness. Conclusions:This study documents poor nutritional status among HIV positive children of 18 months-18 years age group. HIV is an independent and non-modifiable risk factor for poor nutritional outcomes in those who are already infected but an improvement in their nutritional status may significantly decrease their morbidity. Early pediatric HIV testing of exposed or at risk children, followed by appropriate health care for infected children with integration of other child survival interventions like immunization, community participation may improve their nutritional status and survival.